Pathological Left Ventricular Hypertrophy and Stem Cells: Current Evidence and New Perspectives - Maria E. Marketou; Fragiskos Parthenakis; Panos E. Vardas (Hindawi Limited, 2016)
Left ventricular hypertrophy (LVH) is a strong predictor of adverse cardiovascular outcomes. It is the result of complex mechanisms that include not only an increase in protein synthesis and cell size but also proliferating cardiac progenitor cells and the influx of bone marrow-derived cells developing into cardiomyocytes. Stem and progenitor cells are known to contribute to the renewal of adult mammalian cardiomyocytes in case of myocardial injury or pressure and volume overload. They are activated in LVH and play a regulatory role in myocardial repair. They have high proliferative potential and secrete numerous cytokines, growth factors, and microRNAs that play important roles in cell differentiation, cardiac remodeling, and neovascularization. They are mobilized in response to either mechanical or chemical stimuli, hormones, or pharmacologic agents. Another important source of progenitor cells is the epicardial layer. It appears that precursor cells migrate from the epicardium to the myocardium in order to interact with myocardial cells. In addition, migratory cells participate in the formation of almost all cardiac structures in myocardial hypertrophy. Although the pathophysiological mechanisms are still obscure and further studies are required, their properties may open the door to regenerative cell therapy for the prevention of adverse remodeling.